(untitled) (Asian Journal of Medical and Biological Research, 2021)
The present study was carried out to investigate the haemato-biochemical profile during different stages of lactation in local Sahiwal crossbreed dairy cows at Savar area of Dhaka district of Bangladesh. Twenty four local Sahiwal crossbreed cows were selected randomly from different small farms and divided into three groups: early stage lactation (1-3 months), mid stage lactation (4-6 months) and late stage lactation (7-9 months). Blood samples were collected during three stages of lactation. There were no statistical significant (p<0.05) variations observed in hematological parameters amongst the three stage of lactation. Although the packed cell volume (PCV), hemoglobin (Hb) concentration and RBC count were found lowest in early stage of lactation than the other groups. Total leucocyte count (TLC), platelet count (PLT), mean corpuscular volume (MCV) and mean corpuscular haemoglobin (MCH) were recorded within normal limits. Similarly, biochemical parameters were observed statistically non-significant amongst the groups studied. The glucose level was recorded lowest in early stage of lactation; whereas, the protein and creatinine concentrations were slightly higher in this stage. Aspartate aminotransferase (AST), Alanine aminotransferase (ALT) and Alkaline phosphatase (ALP) were not varied amongst the three groups of cows. Data generated during the current study may be useful as reference values for the scientific community. Asian J. Med. Biol. Res. March 2021, 7(1): 1-5